2011
DOI: 10.3945/ajcn.111.015743
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic iron stores are increased as assessed by magnetic resonance imaging in a Chinese population with altered glucose homeostasis

Abstract: Background: Emerging scientific evidence has disclosed a correlation between iron metabolism and type 2 diabetes (T2D). Objective: The objective of this study was to test the hypothesis that body iron stores are higher in a Chinese population with altered glucose homeostasis. Design: Serum iron, ferritin, and soluble transferrin receptor concentrations were measured in 298 subjects, including 70 subjects with normal glucose tolerance (NGT group), 60 subjects with prediabetes (prediabetes group), and 168 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…However, no significant change in Hb was observed in the current study. Clinical studies (2,17) also reported that Hb remained unchanged in DM2 or IGT patients. In addition, hyperglycemia may be also involved in hepcidin regulation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, no significant change in Hb was observed in the current study. Clinical studies (2,17) also reported that Hb remained unchanged in DM2 or IGT patients. In addition, hyperglycemia may be also involved in hepcidin regulation.…”
Section: Discussionmentioning
confidence: 94%
“…In conclusion, the current study suggests that hepcidin can be directly regulated by insulin, and the suppressed liver hepcidin synthesis may be an important reason for the iron overload in DM2. Body iron overload is frequently observed in patients with type 2 diabetes mellitus (DM2) (1,2) or impaired glucose tolerance (IGT) (3,4). Iron overload has been confirmed as an independent factor contributing to the development of DM2 by causing oxidative stress injury in hepatocytes and pancreatic b-cells (5), which may finally lead to insulin resistance (IR) and reduction in insulin extraction and secretion (6).…”
Section: Hepcidin Is Directly Regulated By Insulin and Plays An Impormentioning
confidence: 99%
“…Until now, only tissue iron in the liver has been identified to be associated with systemic insulin action (43,44). AT iron should be evaluated in association with the expression of the different genes involved in iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload in liver can disrupt insulin inhibition of hepatic glucose production, which together in conjunction with reduced hepatic extraction of insulin, leads to peripheral hyper-insulinemia [17]. Zheng and his colleagues [13] noticed that liver iron content was increased in people with T2DM and insulin resistance [14], similarly, Bao and colleagues concluded that increased body iron stores were significantly associated with the risk of T2DM [15].…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%
“…Epidemiological studies showed an association between iron stores and the development of metabolic syndrome [13]. Zheng and colleagues [13] noted that liver iron is increased in people with T2DM and insulin resistance [14]. Moreover, increased body iron stores were significantly associated with risk of T2DM [15].…”
Section: Introductionmentioning
confidence: 99%